2022
DOI: 10.3390/horticulturae8030218
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Freeze-Damage in Grapefruit by Electric Bioimpedance Spectroscopy and Electric Equivalent Models

Abstract: Grapefruit is a cold-sensitive citrus fruit, and freezing can spoil the harvest when the fruit is still on the tree and even later during manufacturing and transport due to inappropriate postharvest management. This study performed a specific Electric Impedance Spectroscopy (EIS) analysis and statistical data treatment to obtain an EIS and Artificial Neural Networks (ANN)-based model for early freeze-damage detection in grapefruit showing a Correct Correlation Rate of 100%. Additionally, Cryo-Field Emission Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Electrical bioimpedance spectroscopy measurements of the flavedo, albedo and pulp in 'Star Ruby' grapefruit were carried out for early freeze-damage detection in grapefruit, showing a Correct Correlation Rate of 100% [279]. Chalupowicz et al [280] used a bacterial cells-based biosensor to follow up P. digitatum colonization in Valencia.…”
Section: Nanosensors For Early Detectionmentioning
confidence: 99%
“…Electrical bioimpedance spectroscopy measurements of the flavedo, albedo and pulp in 'Star Ruby' grapefruit were carried out for early freeze-damage detection in grapefruit, showing a Correct Correlation Rate of 100% [279]. Chalupowicz et al [280] used a bacterial cells-based biosensor to follow up P. digitatum colonization in Valencia.…”
Section: Nanosensors For Early Detectionmentioning
confidence: 99%
“…EIS is an alternative technology to existing methods that is already showing promising results in the agro-food industry [ 37 , 38 ], where it is used for a wide range of applications, such as the assessment of injury healing in fruit plants [ 31 ], grading and quality control of vegetables [ 39 , 40 , 41 ], fruit [ 42 , 43 ], meat [ 44 ], fish [ 45 , 46 ], and honey [ 47 ], as well as for pesticide detection [ 48 ] and the valorization of agro-food waste [ 49 ]. A relationship has also been established between the electrical behavior of biological tissue and changes in its properties due to freezing [ 50 ] or drying [ 40 ]. For example, it was found that, in the low-frequency region, due to the high electrical capacitance of cell membranes, electric current flowed only through the extracellular fluid, which had a relatively high resistance.…”
Section: Resultsmentioning
confidence: 99%
“…When trees are exposed to subfreezing temperatures for extended periods of time, ice can form in the apoplast of wood tissues, causing water to move from the protoplasm to the ectoplasmic space ( Verhoeven et al., 2018 ; Ramirez and Poppenberger, 2020 ). Prolonged exposure can result in a continuous increase in ice crystal volume, puncturing the cell membrane and potentially leading to cell death ( Romero Fogué et al., 2022 ; Mihailova et al., 2020 ; Prerostova et al., 2021 ). In addition to the duration of exposure to freezing temperatures, the rate at which the environmental temperature decreases is another factor that affects ice formation in wood tissues ( Weiser, 1970 ).…”
Section: Introductionmentioning
confidence: 99%